Improving the likelihood of SME survival during financial and economic crises: The importance of TMTs and family ownership for ambidexterity - Consuelo Dolz; María Iborra; Vicente Safón (BRQ Business Research Quarterly, 2019)
In the context of an economic and financial crisis characterized by scarce munificence and high uncertainty, we examine the role of organizational ambidexterity in SMEs survival, and the TMT and ownership characteristics that influence ambidexterity. Our analysis of Spanish manufacturing SMEs in the context of an international economic crisis suggests that: (1) firm survival is associated with ambidexterity; (2) diversity in TMT tenure improves firm ambidexterity and (3) a negative effect exists between family ownership and ambidexterity, but (4) a positive effect exists between family ownership and survival. This study contributes to our understanding of the antecedents of SME ambidexterity by providing a theoretical model that combines the arguments of upper-echelons theory with those found in family-firm research offering an extended view of corporate elites in SMEs. Our research highlights and provides support to the superiority of ambidexterity for survival under external (crisis) and internal (SMEs) restrictions.
Keywords: M10; 650; Family ownership; Organizational ambidexterity; SME; Survival; Top management team